1992
DOI: 10.1136/bmj.304.6828.671
|View full text |Cite
|
Sign up to set email alerts
|

Extended fetal echocardiographic examination for detecting cardiac malformations in low risk pregnancies.

Abstract: Chisholin (GD. Benign prostatic hyperplasia: the best treatment. 1BMI7 1989;299:2 15-6. 2 Neal DE. Irostatectom\-an open or shut case. Br7 Urol 1990;66:449-54. 3 Wrennburg J E, Roos N, Sola L, Schori A, Jalfe R. Use of claims data s\stcms to cvaluatc he:alth care ouitcomes. Mortality and re-operation aftcr prostatectormr. J.1IA 1987;257:933-6. Design-Comparison of extended fetal echocardiography with the standard four chamber view in detecting abnormalities. Extended echocardiography comprised the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
146
1
14

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(173 citation statements)
references
References 10 publications
8
146
1
14
Order By: Relevance
“…Unfortunately, most population studies regarding the use of ultrasonography to detect congenital heart disease have reported low sensitivities for abnormalities of the great arteries [10,12,13,28,41,42,63,64]. Studies documenting higher detection rates emphasized routine visualization of the outflow tracts in addition to the usual four-chamber view [8,22,24,25,27,32,36,37,[65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most population studies regarding the use of ultrasonography to detect congenital heart disease have reported low sensitivities for abnormalities of the great arteries [10,12,13,28,41,42,63,64]. Studies documenting higher detection rates emphasized routine visualization of the outflow tracts in addition to the usual four-chamber view [8,22,24,25,27,32,36,37,[65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…In our country, most fetal examinations are covered by major health insurance organizations. Fetal cardiac examination is standardized using the extended protocol for fetal echocardiography, as previously reported by us [6][7][8][9] . This routinely includes seven sonographic views: (1) transverse view of the upper abdomen; (2) four-chamber view; (3) longitudinal left outflow tract; (4) short-axis view for right outflow tract; (5) longitudinal view for aortic arch and ductus; (6) longitudinal view for systemic veins; and (7) upper axial mediastinal, three-vessel view combined with tracheal location for aortic arch abnormalities.…”
Section: Accepted 21-8-02 Ultrasound In Obstetrics and Gynecologymentioning
confidence: 99%
“…Na nossa série a inclusão dos cortes eixo longo e eixo curto na avaliação do nível I foram determinantes para a detecção de 25% das alterações estruturais e pode explicar a sensibilidade de 72%, em concordância com outros estudos importantes que obtiveram taxas de detecção superiores a 70% 13,14 .…”
Section: Discussionunclassified
“…Congenital heart disease; Echocardiography/diagnostic use; Prenatal diagnosis; Fetal diseases/ ultrasonography; Heart defects, congenital/ultrasonography cular e interrupção do arco aórtico, pois neste plano os grandes vasos não são visualizados e o coração pode ser interpretado como normal na presença destas malformações 13 . Para o completo rastreamento destas malformações é necessária a abordagem de pelo menos dois outros cortes básicos, os eixos longo e curto.…”
Section: Introductionunclassified